Variáveis antropométricas e hemodinâmicas em relação a diferentes níveis e categorias de atividade física - Bueno, Denise Rodrigues; Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Freitas Júnior, Ismael Forte [UNESP]; Rosa, Clara Suemi Costa [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2013)
This study aimed to investigate the relation between physical activity levels (PAL) of hypertensive patients, seeing different do- mains, and, to compare anthropometric variables and blood pressure (BP). The survey was conducted with 192 patients, mean age 63 ± 11 years. The anthropometric variables were body weight, body mass index (BMI) and waist circumference (WC). PAL was estimated using Baecke ́s questionnaire and categorized in four domains (OPA = occupational; leisure time = LTPA; locomotion = LPA and Total PA). Student t test unpaired was applied for comparisons between active and insufficiently active. Differences between active and sedentary in relation to anthropometry and resting blood pressure were observed for the LTPA, LPA and Total PA and significant negative correlations were observed between LPA and Total PA with systolic BP (p<0,05). Conclusion: the LPA and LTPA were associated with resting BP in hypertensive. No differences in BMI and WC among physically active and insuffi- ciently active were found.

O objetivo do presente estudo é investigar relações entre nível de atividade física (NAF) e pressão arterial (PA) de hipertensos, considerando diferentes domínios, e comparar variáveis antropométricas e PA entre NAFs. A pesquisa foi realizada com 192 indivíduos de idade média de 63 ± 11 anos. Variáveis antropométricas foram peso corporal, índice de massa corporal (IMC) e circunferência de cintura (CC). O NAF foi estimado, aplicando-se questionário de Baecke e categorizado em quatro domínios (ocupacional=AFO; tempo livre=AFTL; locomoção=AFL; e total=AFT). O teste T de Student não pareado comparou médias entre ativos e insuficientemente ativos, e o teste de correlação de Pearson analisou correlação entre variáveis, quando contínuas. Indivíduos ativos para AFTL, AFL e AFT apresentaram menor PA, e correlações negativas com pressão sistólica foram observadas para AFL e AFT (p<0,05). Conclusão: AFL e AFTL estão relacionadas à PA de repouso em hipertensos. Não houve diferença em IMC e CC, comparando IA e AT.
Anthropometric and hemodynamic variables in relation to different physical activity levels and domains
Keywords: Physical activity; Hypertension; Anthropometry; Atividade física; Hipertensão; Antropometria